An efficient, open-bid procurement auction for small-scale electricity markets. (15th May 2022) - Lange, Sebastian; Sokolowski, Peter; Yu, Xinghuo
Abstract: Despite early calls to investigate the application of Vickrey auctions in electricity markets, academic literature still provides little insight into the matter. Similarly, despite general auction-theoretic literature discussing various advantages of employing revealed rather than sealed bidding procedures, publications on electricity market auctions rarely even mention differences between these opposing features. This paper marries these neglected features into a new auction model for electricity markets. We propose a novel open-bid, descending-clock auction capable of handling inter-bidder dependencies such as thermal line limits. A novel set of termination criteria ensures that our proposed auction facing markets with power balance and generator capacity constraints and thermal line limits, preserves truthful bidding as a dominant strategy, which, if employed by all bidders, allocates supply efficiently constituting an ex-post perfect equilibrium. Furthermore, we discuss known disadvantages of Vickrey–Clarke–Groves type auctions in the context of our proposed auction applied in electricity markets. Highlights: Proposition of a novel auction design considering electricity grid constraints. Given quasi-linear utility, truthful bidding is weakly dominant utilising open bids. Truthful bidding by all bidders results in efficient supply allocation. Discussion of real-world electricity market design impacting auction properties.